Quality of Life of Children Between 5 and 7 Years and Affecting Factors - Halime Dağtekin; Nejla Canbulat Şahiner (Çocuk Dergisi)
Aim: This study has been carried out as a descriptive research in order to determine children’s quality of life and the factors affecting their quality of life. Methods: The research data were obtained from 260 children between the ages of five and seven years and their parents in Türkiye’s Karaman province between September 2019-June 2020. Data were collected using a questionnaire form and the child and parent forms for the Quality of Life Scale for Children. The study used frequencies, percentages, means, min and max values, Cronbach’s alphas, t test results, ANOVA testing, the Mann Whitney U-test, and regression analyses to analyze the data, with the Bonferonni correction test being used in further analyses. Results: Of the students examined within the scope of the study, 53.1% were determined to be girls and 50% to be six years old; their mean body mass index (BMI) was identified as 15.31 (SD = 2.61). The mean score from the child version of the Quality of Life Scale for Children was seen to be 71.23 (SD = 13.28), and the mean score from the parent version was seen to be 65.69 (SD = 14.11). The children’s quality of life was determined to be affected by family income status, parents’ educational status, the presence of chronic diseases in the parents, and the presence of any disease diagnosed in the child. Conclusion: According to the research results, the children were found to have high mean scores for their overall quality of life, while the children’s quality of life scores as evaluated by the parents were found to be at a medium level. The lowest mean for the children’s and parents’ forms were found to occur in the sub-dimension of emotional functionality. The children’s quality of life was observed to vary according to certain variables such as the family income level, parents’ educational level, the presence of a chronic disease in the parents, and the presence of any disease diagnosed in the child.